The association between bedtime at night and diabetes in US adults: Data from National Health and Nutrition Examination Survey (NHANES) 2015-March -2020 pre-pandemic. - Shayuan Ouyang; Yinghua Su; Ning Ding; Yingjie Su; Liudang He (PLoS ONE)
Objective The purpose of this study was to investigate the relationship between bedtime at night and the risk of diabetes in adults. Methods We extracted data from 14,821 target subjects from the NHANES database for a cross-sectional study. The data on bedtime came from the question in the sleep questionnaire: "What time do you usually fall asleep on weekdays or workdays?". Diabetes was defined as fasting blood sugar ≥ 126mg/dL, or glycohemoglobin ≥ 6.5%, or 2-hour Oral Glucose Tolerance Test blood sugar ≥ 200mg/dL, or taking hypoglycemic agent and insulin, or self-reported diabetes mellitus. A weighted multivariate logistic regression analysis was conducted to explore the relationship between bedtime at night and diabetes in adults. Results From 19:00 to 23:00, a significantly negative association can be found between bedtime and diabetes(OR, 0.91 [95%CI, 0.83, 0.99]). From 23:00 to 02:00, The relationship between the two was positive(OR, 1.07 [95%CI, 0.94, 1.22]), nevertheless, the P values was not statistically significant(p = 0.3524). In subgroup analysis, from 19:00-23:00, the relationship was negative across genders, and in males, the P-values were still statistically significant(p = 0.0414). From 23:00-02:00, the relationship was positive across genders. Conclusion Earlier bedtime (before 23:00) increased the risk of developing diabetes. And this effect was not significantly different between male and female. For bedtime between 23:00-2:00, there was a trend of increasing the risk of diabetes as the bedtime was delayed.